Experiencing Positive Religious Coping in the Process of Divorce: A Qualitative Study - Simonič, Barbara (Journal of religion and health, 2017)
Divorce is one of the more stressful and psychologically challenging experiences for spouses and whole families. After divorce, a new era begins, when it is necessary to re-adapt to life and during which hard feelings also emerge. During the process of divorce, successful emotional adaptation to the new situation is of great significance. Religion or spirituality can be a powerful source of help for an individual coping with stressful situations brought up by divorce. This study aimed to explore if and how divorcees experience the burden of divorce and along with it the relationship with God (within Catholic tradition) as a source of positive support in coping with divorce. We conducted open semi-structured interviews with 11 participants. With empirical phenomenological analysis, we built a general description of the investigated experience which entails three areas of experience: experiencing the burden of divorce, which is related to experiencing the relationship with God and the ways of spiritual coping with divorce, and experiencing the effects of religious coping with divorce. The result of this research can be used in evidence-based psychosocial (e.g. psychotherapy, counselling) and spiritual help for individuals in comprehensive care after divorce.